2014
DOI: 10.1002/j.2168-0159.2014.tb00121.x
|View full text |Cite
|
Sign up to set email alerts
|

33.1: Channel‐Etched C‐Axis Aligned Crystalline Oxide Semiconductor FET Using Cu Wiring

Abstract: A channel-etched IGZO field-effect transistor (FET) using Cu wiring was fabricated. Because little Cu is diffused into a c-axis aligned crystalline oxide semiconductor (CAAC-OS), which is c-axis aligned crystalline IGZO, the use of the CAAC-OS provides favorable characteristics for a channel-etched FET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…In an OS‐FET, stability of a back channel is required. Employing the CAAC structure is a means of increasing stability, and we have therefore examined modifications of the CAAC structure to further increase the stability of the back channel . OS‐FETs are operated by the accumulation of electrons that are the major carriers.…”
Section: Buried Channel Structurementioning
confidence: 99%
“…In an OS‐FET, stability of a back channel is required. Employing the CAAC structure is a means of increasing stability, and we have therefore examined modifications of the CAAC structure to further increase the stability of the back channel . OS‐FETs are operated by the accumulation of electrons that are the major carriers.…”
Section: Buried Channel Structurementioning
confidence: 99%
“…Our research group previously reported on back-channel-etched (BCE) and top-gate self-aligned (TGSA) field-effect transistors (FETs) with oxide semiconductor (OS) active layers [1][2][3][4][5][6]. OSbased FET (OSFET) technologies have recently been widely applied.…”
Section: Introductionmentioning
confidence: 99%
“…The authors previously developed OS FETs with back-channeletched (BCE) and top-gate self-aligned (TGSA) structures [1][2][3][4][5][6]. BCE OS FETs can be fabricated using fewer masks than those required for TGSA OS FETs.…”
Section: Introductionmentioning
confidence: 99%